Influence of Blanching, Frying and Storage on the Physicochemical Properties and Shelf Life of Fried Taro (Colocasia Esculenta) Chip - Nguyen Phuoc Minh (Journal of Global Pharma Technology, 2016)
Taro (Colocasia esculanta) tubers have the great importance of functional foods. Taro tubers are important sources of carbohydrates as an energy source. Taro tubers provide a number of desirable nutritional and health benefits such as anticancer activity, phenolic acid and phytochemicals. Taro deteriorates rapidly as a result of its high moisture. The high perishability of taro during storage remains a major constraint. It is widely cooked by deep frying and consumed in forms of French fries and chips. The major challenge for the food industry is to produce low fat fried product with desirable texture, color and ﬂavor. This research has been focused on different parameters of blanching, drying for minimum oil absorption and sensory palatability while maintaining the most phytochemical components such as total phenolic, total flavonoid and anthocyanin; extending product shelf life during packaging and preservation. Results revealed that blanching 95oC in 30 seconds with ascorbic acid of 0.15 g/100g taro, frying 2.0 cm of taro chip in soybean oil heating at 155oC in 2 minutes was appropriated. Fried taro chip could be preserved for 12 weeks under vaccum at 4oC. Moisture and oil content, as well as colour and texture are important quality attributes of fried taro products. Frying of taro chips is carried out to convert the tubers to value added products. Frying method brings out unique flavor and texture to the products that improve their overall acceptability.Keywords: Taro chip, Blanching, Frying, Shelf life, Anthocyanin, flavonoid.